Faktor-Faktor Yang Mempengaruhi Pemberian Imunisasi Dasar Lengkap Pada Bayi di UPTD Puskesmas Sungai Raya Aceh Timur Tahun 2024 - Cut Devi Indriani; Rumondang Sitorus; Nurmalina Hutahaean (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Accination actively seeks to create/enhance a person's immunity to disease. Vaccination protects children from several immunisation-preventable diseases (VPDs). Some of the infectious diseases included in VPDs are tuberculosis, diphtheria, tetanus, hepatitis B, whooping cough, measles, polio, and meningitis. Vaccinated children will be protected from dangerous diseases that can cause injury or death. This study is included in analytical observational research, which does not conduct treatment on research subjects with the aim of providing a clearer picture of the problem in the subject. This type of research is a type of survey with a cross sectional design or where the data collection process is carried out at the same time between independent variables, namely factors that influence the provision of complete basic immunisation in infants. Based on the table, it can be seen that the majority of mothers have a high school education as many as 30 people, the majority of mothers who work as housewives as many as 46 people, the majority of mothers have less knowledge as many as 52 people, the majority of mothers with incomplete basic immunisation as many as 56 people.